A two-way coupled FSI model for the rapid evaluation of accidental loads following ship hard grounding. (July 2022) - Taimuri, Ghalib; Kim, Sang Jin; Mikkola, Tommi; Hirdaris, Spyros
Abstract: The assessment of structural crashworthiness following ship grounding events should consider the influence of multi-physics on dynamic response. To date, this has been achieved by computationally expensive approaches combining explicit 3D FEA with hydrodynamic solvers (e.g. Conti et al. (2021); Kim et al. (2021)). To offer an alternative, this paper presents a rapid six degree of freedom (6-DoF) two-way coupled fluid–structure interaction (FSI) model that could be used for the rapid evaluation of ship dynamic response and structural crashworthiness during hard grounding events. The time domain solution is based on a simplified contact analysis model that combines the external dynamics idealization of Taimuri et al. (2020) with an extended version of the internal mechanics analytical formulation of Simonsen (1997a) and Sun et al. (2017). The plate cutting angle is calibrated based on the rock geometry and hull indentation. A ray-tracing algorithm that utilizes panels and the tip of a conical rock is implemented to idealize hull penetration. The model is numerically validated by comparing results against LS-DYNA simulations for a box-shaped barge of double bottom configuration and a passenger vessel. Parametric studies demonstrate that longitudinal and vertical forces produced by different models compare well. However, the lateral forces for the study case of a passenger ship progressing along a straight path are shown to be underestimated. This is because the proposed method (i) does not allow for the influence of lateral loading on longitudinal hull members and (ii) overestimates the forces in regions of extreme curvature (e.g. fore shoulder, bow and boundaries of the hull).